Analysis of the Thermal Characteristics of Surrounding Rock in Deep Underground Space - Liu Chen; Jiangbo Li; Fei Han; Yu Zhang; Lang Liu; Bo Zhang (Advances in Civil Engineering)
With the development of society, the economy, and national security, the exploitation of deep underground space has become an inevitable trend in human society. However, high-temperature-related problems occur in deep underground spaces. The high temperature of deep underground space is essentially influenced by the thermal characteristics of the surrounding rock. According to the mathematical model of heat transfer of the surrounding rock in deep underground space, similar criteria numbers are established. Experiments were carried out to investigate the thermal characteristics of the surrounding rock. The distribution characteristics of temperature were determined by the Fourier number (Fo) and Biot number (Bi), and the effects of heat transfer time, airflow velocities, and air temperature and radial displacement on the distribution characteristics of temperature were studied. The results indicate that the surrounding rock temperature decreases with long heat transfer times, high airflow velocities, and low air temperatures.